IMPRESI PRODUK DOMESTIK REGIONAL BRUTO TERHADAP TINGKAT KEMISKINAN DI KABUPATEN LOMBOK TENGAH - Ibrahim, Ibrahim; Pratama, Inka Nusamuda (FISIP Universitas Malikussaleh, 2024)
Gross Regional Domestic Product (GRDP) is one of the important measurements in measuring the economic welfare of a region or area. GRDP describes the total value of goods and services produced in a region in a certain period, usually in a year. GRDP includes all types of economic activities that occur in the region, including activities in the agricultural, fisheries, industrial, trade, services and other sectors. The purpose of this study was to determine the impression of Gross Regional Domestic Product on poverty levels in Central Lombok District. The results of this study indicate that: Gross Regional Domestic Product (GRDP) plays a significant role in reducing poverty rates in Central Lombok District. The distribution of Gross Regional Domestic Product must be evenly distributed throughout all levels of society, including the poor in Central Lombok Regency. Development should be directed at expanding the benefits of the Gross Regional Domestic Product (GRDP) to all residents in Central Lombok Regency. Efforts are needed to increase the growth of the Gross Regional Domestic Product (GRDP) in all business sectors by utilizing the existing potential.Produk Domestik Regional Bruto (PDRB) adalah salah satu ukuran penting dalam mengukur kesejahteraan ekonomi suatu wilayah atau daerah. PDRB menggambarkan nilai total produksi barang dan jasa dalam suatu wilayah dalam periode tertentu, biasanya dalam setahun. PDRB mencakup semua jenis kegiatan ekonomi yang terjadi di wilayah tersebut, termasuk kegiatan sektor pertanian, perikanan, industri, perdagangan, jasa, dan sektor lainnya. Tujuan dalam penelitian ini adalah untuk mengetahui impresi Produk Domestik Regional Bruto terhadap tingkat kemiskinan di Kabupaten Lombok Tengah. Hasil penelitian ini menunjukkan bahwa: Produk Domestik Regional Bruto (PDRB) memainkan peran yang signifikan dalam menurunkan tingkat kemiskinan di Kabupaten Lombok Tengah. Distribusi Produk Domestik Regional Bruto harus merata di seluruh lapisan masyarakat termasuk golongan miskin di Kabupaten Lombok Tengah. Pembangunan harus diarahkan untuk memperluas manfaat dari Produk Domestik Regional Bruto (PDRB) ke seluruh penduduk di Kabupaten Lombok Tengah. Diperlukan upaya untuk meningkatkan pertumbuhan Produk Domestik Regional Bruto (PDRB) di semua sektor lapangan usaha dengan memanfaatkan potensi yang ada.